Stigma and posttraumatic growth among COVID-19 survivors during the first wave of the COVID-19 pandemic in Malaysia: a multicenter cross-sectional study - Azman, Nazirah; Nik Jaafar, Nik Ruzyanei; Leong Bin Abdullah, Mohammad Farris Iman; Abdul Taib, Nur Iwana; Mohamad Kamal, Nurul Ain; Abdullah, Muhammad Najib; Dollah, Siti Nordiana; Mohamed Said, Mohd Shahrir (Frontiers in Psychiatry, 2023)
Background Contracting COVID-19 can cause negative and distressing psychological sequelae, but traumatic stressors may also facilitate the development of positive psychological change beyond an individual’s previous level of adaptation, known as posttraumatic growth (PTG). As a result, studies have investigated the negative effects of COVID-19 on mental health, but data on PTG among patients who have recovered from COVID-19 remains limited. This study aims to evaluate the level of PTG and its associations with stigma, psychological complications, and sociodemographic factors among COVID-19 patients 6 months post-hospitalization. Method A cross-sectional online survey of 152 COVID-19 patients was conducted after 6 months of being discharged from Hospital Canselor Tuanku Muhriz, MAEPS Quarantine Center, or Hospital Sungai Buloh, Malaysia. Patients completed a set of questionnaires on sociodemographic and clinical data. The Posttraumatic Growth Inventory (PTGI-SF) was used to assess the level of PTG, the Kessler Psychological Distress (K6) was used to measure the degree of psychological distress, the General Anxiety Disorder-7 (GAD-7) was used to evaluate the severity of anxiety symptoms, the Patient Health Questionnaire (PHQ-9) was used to assess the severity of depression symptoms, and the Explanatory Model Interview Catalog Stigma Scale (EMIC-SS) was used to record the degree of perceived stigma toward COVID-19. Results The median PTGI SF score of the respondents was 40.0 (Interquartile range 16.0). Multivariable general linear model with bootstrapping (2,000 replications) revealed factors that significantly predicted PTG, which were at the higher level of the perceived stigma score, at 37 (B = 0.367, 95% CI = 0.041 to 0.691, p = 0.026), among the Malay ethnicity (B = 12.767, 95% CI 38 = 7.541 to 17.993, p < 0.001), retirees (B = −12.060, 95% CI = −21.310 to −2.811, p = 0.011), and those with a history of medical illness (B = 4.971, 95% CI = 0.096 to 9.845, p = 0.046). Conclusion Experiencing stigma contributed to patients’ PTG in addition to psychosocial factors such as ethnicity, history of medical illness, and retirement.